Soft System Methodology (SSM) Analysis to Increase the Number of Prospective Students - Nikhlis, Neilin; Iriani, Ade; Hartomo, Kristoko Dwi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
The competition between campus, whether it’s a public college and private college in Central Java, is very tight with the increasing number of interested students for prospective students from various regions. The close competition requires many campuses to compete to provide the best facilities and services. The research objective is expected to support the "XY" university promotion strategy to help the university in the knowledge capture process. Data collection was carried out using the group discussion forum (FGD) method with a structured interview process for university leaders, university officials, marketing departments, and students. The technique used in this study is a soft system methodology (SSM). The results of this study model knowledge capture (KC) on the "XY" university promotion strategy and produce knowledge documentation that provides benefits in making policy strategies and has an impact on increasing the number of prospective new college students by optimizing digital marketing.